Major concerns and issues in burn survivors in Australia. Issue 2 (6th April 2014) - Dowda, Deborah J; Li, Frank
Abstract: Burn injury significantly impacts the victim's long-term quality of life, both physically and psychosocially. This prospective, observational study aimed to assess the physical and psychological health status in adult burn survivors in Sydney Australia using the Burns Specific Health Scale-Brief Version (BSHS-B) questionnaire, together with analysis of the baseline demographic data collected from medical records. A total of 24 adult acute burn victims admitted consecutively to the Burns Unit at Concord Repatriation General Hospital, Sydney, Australia between March 2007 and February 2009 fulfilled the inclusion criteria and participated in the study. The BSHS-B questionnaire (which includes nine domains or subscales) was administered to all 24 participants in person at time of discharge and by mail 6, 12, and 24 months post discharge. By 12 months, 11 participants dropped out and the final analysis was performed on the remaining 13 participants. The analyzed results showed that: 1) Perceived return to work was the only variable that continued to change with time at 12 months after discharge ( P < 0.01); 2) At 12 months; return to work was significantly correlated with simple functional ability ( P < 0.05), heat sensitivity ( P < 0.01), and treatment regimes ( P < 0.05), but no longer with affect and body image as demonstrated at 6 months. In summary, our findings have shown that the perception of returning to work changes significantly with time post discharge and this perception is affected by certain subscales of the BSHS-B. Given that return to work is one of the most important outcome concerns and issues of recovery for adult burn injury victims and families, it is essential that therapists be aware of the factors influencing return to work and address these factors through a comprehensive rehabilitation program.